Using Nonword Repetition Tasks for the Identification of Language Impairment in Spanish-English Speaking Children: Does the Language of Assessment Matter? - Gutiérrez-Clellen, Vera F. (2010)
The purpose of this study was twofold: (a) to evaluate the clinical utility of a verbal working memory measure, specifically, a nonword repetition task, with a sample of Spanish-English bilingual children and (b) to determine the extent to which individual differences in relative language skills and language use had an effect on the clinical differentiation of these children by the measures. A total of 144 Latino children (95 children with typical language development and 49 children with language impairment) were tested using nonword lists developed for each language. The results show that the clinical accuracy of nonword repetition tasks varies depending on the language(s) tested. Test performance appeared related to individual differences in language use and exposure. The findings do not support a monolingual approach to the assessment of bilingual children with nonword repetition tasks, even if children appear fluent speakers in the language of testing. Nonword repetition may assist in the screening of Latino children if used bilingually and in combination with other clinical measures.